Late Bronze Age in Alcáçova de Santarém (Portugal) - Arruda, Ana Margarida (2018)
The field work that took place in the restaurant area in Jardim das Portas do Sol (Alcáçova de Santarém) recovered well-preserved archaeological layers dated to the Late Bronze Age, lying directly underneath the Iron Age phase. The excavation made it possible to collect an important set of ceramics that incorporate printed and incised decoration, which can be easily decoration related to the Cogotas 1 cultural background. Burnished decorations, with grooves on the inner surface and outer strips, are less common. The formal repertoire does not deviate from what is known about the Late Bronze Age in central and southern Iberian Peninsula. The data allow us to propose a chronology centered in the early 1st Millennium BCE for this occupation.